Work Stress, Job Burnout, and Turnover Intention among Micro, Small, and Medium Finance Company’s Employee - Yusnita, Nancy; Gursida, Hari (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2024)
Research aim: The purpose of this study is to find efforts to reduce the turnover intention of an employee by examining the factors that become antecedents of the turnover intention of an employee, namely work stress and job burnout. Design/Methode/Approach: Quantitative approach with survey method, using regression analysis (path analysis) and quantitative data (from questionnaires). Finding: This study reveals that work stress and job burnout positively influence turnover intention, with job burnout mediating the relationship between work stress and turnover intention, while life stressors, feeling ineffective in dealing with others at work, and actively seeking a new job are identified as the most influential factors. Theoretical contribution/Originality: The theoretical contribution of this research lies in its special emphasis on the influence of perceived outcomes of stress and the importance of harmonious relationships between coworkers in reducing the impact. Practitioner/Policy implication: Concerning the turnover intention of their employee to decrease the turnover of employees by reducing stress levels and reducing job burnout in employees. Research limitation: This study only used samples from branch offices in Java Island, as well as its examination of only three variables (Work Stress, Job Burnout, and Turnover Intention). We recommend further research to use a wider sample.